Organisational citizenship behaviour and employee engagement in IT employees - MONICA, DR. BENITA. S.; KUMAR R, MR. RANJITH (The journal of contemporary issues in business and government, 2020)
The study focuses on understanding the association between organisational citizenship behaviour and employee engagement in the IT industry. Employee engagement is studied with two dimensions namely job engagement and organisational engagement. Convenience sampling method is used to collect data from 62 employees. Multiple linear regression is used to analyse the data. The results prove that both job engagement and organisational engagement are significant positive predictors of above citizenship behaviour. Suggestions for incorporating employee engagement activities in the workplace is provided for HR managers.